A Hybrid Conditional GAN Design for Image-to-Image Translation Integrating U-Net and ResNet - Hariri, Khaled Al; Paşaoğlu, Muhammet; Arıcan, Erkut (Fırat University, 2025)
Image-to-image translation is one of the major image processing tasks in the computer vision field that can be utilized in many types of applications such as style transfer, image enhancement, and more. This study introduces a novel approach for image-to-image translation based on a conditional generator adversarial network with a new hybrid generator architecture that combines the U-Net and ResNet architectures. This combination allows the model to benefit from both of their advantages due to their high compatibility. The discriminator uses the PatchGAN architecture for patch-wise discrimination. The model was evaluated by using the SSIM and PSNR which are standard metrics for image quality evaluation. The results are also compared to previous work that uses the same evaluation criteria and datasets. Furthermore, a public survey was conducted in which the participants were asked to choose the image that most closely resembled the target image between the proposed model and another study. The outcome of both the evaluation metrics and the public survey successfully demonstrated that the proposed image-to-image translation method is superior to that of previous studies.

Görüntüden görüntüye dönüşüm, bilgisayarla görme alanının temel görüntü işleme görevlerinden biri olup, stil transferi, görüntü iyileştirme ve benzeri birçok uygulamada kullanılabilmektedir. Bu çalışmada, koşullu üretici çekişmeli ağlara (Conditional GAN) dayalı ve U-Net ile ResNet mimarilerini bir araya getiren hibrit bir üretici mimarisi üzerine kurulu yeni bir yaklaşım sunulmaktadır. Bu birleşim, yüksek uyumlulukları sayesinde modelin her iki mimarinin avantajlarından yararlanmasına olanak sağlamaktadır. Ayırt edici ağ ise PatchGAN mimarisi üzerine inşa edilerek yama bazlı ayrım yapmaktadır. Modelin performansı, görüntü kalitesi değerlendirmesinde standart kabul edilen SSIM ve PSNR metrikleri kullanılarak ölçülmüş, ayrıca aynı ölçütler ve veri kümeleri üzerinden değerlendirilen önceki çalışmalarla karşılaştırılmıştır. Bunun yanı sıra, katılımcılardan önerilen modelin çıktıları ile başka bir çalışmanın çıktıları arasından hedef görüntüye en çok benzeyeni seçmelerinin istendiği bir kamuoyu anketi de yapılmıştır. Hem değerlendirme metriklerinden hem de kamuoyu anketinden elde edilen bulgular, önerilen görüntüden görüntüye dönüşüm yöntemimizin önceki çalışmalara kıyasla üstün olduğunu açıkça ortaya koymaktadır.
U-Net ve ResNet Entegrasyonu ile Görüntüden Görüntüye Dönüşüm için Hibrit Koşullu GAN Tasarımı
Keywords: Automated Software Engineering; Otomatik Yazılım Mühendisliği; Software Architecture; Yazılım Mimarisi; Reinforcement Learning; Pekiştirmeli Öğrenme; Software Engineering (Other); Yazılım Mühendisliği (Diğer)